Kajian Hukum Penahanan Terhadap Pelanggaran Qanun Nomor 12 Tahun 2003 Tentang Minuman Khamar dan Sejenisnya Menurut KUHAP (StudiKasus di MahkamahSyariah Kota Subulussalam) - Aman, Aman (Universitas Islam Sumatera Utara, 2022)
In practice, it is not easy to realize effective law enforcement, because there are many factors that influence it, both internal and external factors. However, creating conditions for effective law enforcement is not impossible, as long as there is seriousness and hard work from all parties, including the government, the private sector and the community.Therefore, the urgent thing to do is to make improvements in various sectors, both from the system and from the human resource factor, so that the performance and quality of law enforcement in the future can meet the expectations of the community.Law enforcers of Qanun No. 12 2003, among others, consist of Wilayatulhisbah, who is in charge of supervising, fostering, and advocating for the implementation of laws and regulations in the field of Islamic Shari'a in order to carry out amarma'rufnahimunkar, the Police as Investigators whose scope of functional duties is includes pre-emptive, preventive, non-judicial repressive and pro-judicial repressive actions in the field of general police duties and the enforcement of Islamic Shari'a, the Prosecutor as a Public Prosecutor with the authority to carry out special duties in the field of Islamic Shari'a, implementing the determinations and decisions of the Judges of the Syar'iah Court, and Judges The Sharia Court, whose terms and procedures for the appointment, dismissal and execution of their duties are stipulated by law.The procedural legal process stipulated in the implementation of Qanun Number: 12 2003 is still based on the Criminal Procedure Code. This is in accordance with Article 37 of Qanun No. 12 of 2003 and Article 32 of Qanun No. 13 of 2003 which states that: